ANALISIS PERBANDINGAN PEMANFAATAN VIRTUAL ACCOUNT DAN TRANSFER PADA KARYAWAN PONDOK PESANTREN MODERN SAHID DAN KARYAWAN INSTITUT AGAMA ISLAM SAHID BOGOR - Devi Andriani; Tubagus Rifqy Thantawi; Azizah Mursyidah (SAHID BANKING JOURNAL, 2022)
The background of this research is the use of virtual accounts and transfers to employees of the Sahid Modern Islamic Boarding School and employees of the Sahid Islamic Institute in Bogor. The aim is to compare the benefits of virtual accounts and transfers. This study used a quantitative method, the subject of research was at the Sahid Modern Islamic Boarding School and the Sahid Islamic Institute, Bogor. The more modern the digital tools, the easier the transactions between the use of virtual accounts and transfers. This study aims to compare the benefits of virtual accounts and transfers. The results of this study indicate that in the use of virtual accounts and transfers at the Sahid Modern Islamic Boarding School, a value of 0.791 is obtained, which means greater than 0.05 and the use of virtual accounts and transfers at the Sahid Islamic Institute of Bogor, a value of 0.586 is greater than 0. 05. So it can be concluded, the significance value (2-tailed) obtained from the results of the independent sample t-test is greater than > 0.05. Then Ho is accepted and Hi is rejected, meaning that there is no difference in comparison of the utilization of Islamic bank facilities in terms of virtual accounts and transfers to employees of the Sahid Modern Islamic Boarding School and the Sahid Bogor Islamic Institute.